2016
DOI: 10.1080/10986065.2016.1219930
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Limitations in Curricular Presentations of Area Measurement: One Nation’s Challenges

Abstract: Research has found that elementary students face five main challenges in learning area measurement: (1) conserving area as a quantity, (2) understanding area units, (3) structuring rectangular space into composite units, (4) understanding area formulas, and (5) distinguishing area and perimeter. How well do elementary mathematics curricula address these challenges? A detailed analysis of three U.S. elementary textbook series revealed systematic deficits. Each presented area measurement in strongly procedural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In the classroom, textbooks offer opportunities to learn (OTL) mathematics (Hong, Choi, Runnalls, & Hwang, ; Otten et al, ; Smith, Males, Dietiker, Lee, & Mosier, ; Smith et al, ). OTL is often defined as whether or not students have had the opportunity to study a particular topic or learn how to solve a particular type of problem (Floden, ; Liu, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the classroom, textbooks offer opportunities to learn (OTL) mathematics (Hong, Choi, Runnalls, & Hwang, ; Otten et al, ; Smith, Males, Dietiker, Lee, & Mosier, ; Smith et al, ). OTL is often defined as whether or not students have had the opportunity to study a particular topic or learn how to solve a particular type of problem (Floden, ; Liu, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…United States eighth‐grade students’ performance in measurement was weaker than any other content area on the National Assessment of Educational Progress and the Third International Mathematics and Science Study (Mullis, Martin, Foy, & Arora, ; Thompson & Preston, ), indicating that students may need additional mathematical tasks and instruction that reflect their developmental thinking on the matter. We chose the topic of area measurement in geometry because it is one commonly used domain of measurement in everyday life (Outhred & Mitchelmore, ), it plays a transitional role between length and volume measurements, and it forms a foundation for more advanced mathematics, ranging from fractions to calculus (Smith, Males, & Gonulates, ). Studies have shown that students often rely solely on area formulas, without understanding how or why they work (Baturo & Nason, ; Zacharos, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to understand the numerical result of area formulae, students are required to reconstruct their understanding of multiplication as multiplicative composition (Confrey, 2012;Lehrer, 2003;Smith et al, 2016). That is, multiplication of two 1D lengths produces area.…”
Section: Understanding the Numerical Resultsmentioning
confidence: 99%
“…These objectives state that middle school students should be able to apply area formulae to solve authentic problems, for example, "estimating and working out the area of a vegetable garden in square metres and calculating how much sugarcane mulch to buy to cover it" (ACARA, 2016, p. 17). Second, area measurement has applications in other school disciplines, particularly in science and technology (Huang & Witz, 2011;Smith, Males, & Gonulates, 2016), as well as in vocational subjects. Finally, the reasoning that students develop while learning area measurement can be applied in the learning of other mathematical strands such as operations with numbers, volume, multiplication, fractions, probability, algebraic multiplication, enlargement, and calculus (Davydov, Gorbov, Mukulina, Savelyeva, & Tabachnikova, 1999;Dougherty & Zilliox, 2003;Fernández, De Bock, Verschaffel, & Van Dooren, 2014;Hirstein et al, 1978;Kordaki & Potari, 1998;Outhred & Mitchelmore, 2000;Sarama & Clements, 2009;Tan Sisman & Aksu, 2016).…”
Section: Introductionmentioning
confidence: 99%